Phase II trial of sorafenib and erlotinib in advanced pancreatic cancer. (12th February 2014) - Cardin, Dana B.; Goff, Laura; Li, Chung‐I; Shyr, Yu; Winkler, Charles; DeVore, Russell; Schlabach, Larry; Holloway, Melanie; McClanahan, Pam; Meyer, Krista; Grigorieva, Julia; Berlin, Jordan; et al.
Abstract This trial was designed to assess efficacy and safety of erlotinib with sorafenib in the treatment of patients with advanced pancreatic adenocarcinoma. An exploratory correlative study analyzing pretreatment serum samples using a multivariate protein mass spectrometry‐based test (VeriStrat®), previously shown to correlate with outcomes in lung cancer patients treated with erlotinib, was performed. Patients received sorafenib 400 mg daily along with erlotinib 150 mg daily with a primary endpoint of 8‐week progression free survival (PFS) rate. Pretreatment serum sample analysis by VeriStrat was done blinded to clinical and outcome data; the endpoints were PFS and overall survival (OS). Difference between groups (by VeriStrat classification) was assessed using log‐rank P values; hazard ratios (HR) were obtained from Cox proportional hazards model. Thirty‐six patients received study drug and were included in the survival analysis. Eight‐week PFS rate of 46% (95% confidence interval (CI): 0.32–0.67) did not meet the primary endpoint of a rate ≥70%. Thirty‐two patients were included in the correlative analysis, and VeriStrat "Good" patients had superior PFS (HR = 0.18, 95% CI: 0.06–0.57; P = 0.001) and OS (HR = 0.31 95% CI: 0.13–0.77, P = 0.008) compared to VeriStrat "Poor" patients. Grade 3 toxicities of this regimen included fever, anemia, diarrhea, dehydration, rash, and altered liver function. This study did not meet the primary endpoint, and this combination will not be further pursued. In this small retrospective analysis, the proteomic classification was significantly associated with clinical outcomes and is being further evaluated in ongoing studies.